Estimation on the attractiveness of public transport: Vilnius city case - Jarašūnienė, Aldona; Engelaitis, Rytis (Business: Theory and Practice, 2025)
The paper analyses the attractiveness problems of urban public transportation in the context of promoting sustainable mobility and multimodality. The article is based on the methods of scientific literature and analysis and qualitative research analysis. The analytical-methodical section of the article discusses the principles of sustainable mobility and multimodality, assess the possibilities of their application. In the research section, the expert analysis that evaluates Vilnius public transport attractiveness is presented, and affecting problems are assessed and considered. Re-search results have shown that experts agree on the issues (factors) that affect the attractiveness of public transport. These factors have been ranked in order of priority and relevance from 1 (big-gest problem) to 10 (smallest problem). In conclusion, the paper presents a structural model which aims to promote and increase the attractiveness of public transport system.